MARKER TNF -308G/A IN PATIENTS WITH RELATIVE BLADDER CANCER - Elmamatov Obid Nurmamatovich; Rakhimov Nodir Makhammatkulovich; Shahanova Shahnoza Shavkatovna (Scholar Express Journals, 2023)
The aim of the study was to determine the TNF- gene polymorphism in the blood of patients with stage T1N0M0 bladder cancer and to establish their relationship with the grade G malignancy in case of disease recurrence. The study included data from 130 patients with stage T1NoMo bladder cancer: with disease recurrence in 66 patients (main group) and 64 patients with bladder cancer without disease recurrence (control group), including 75 men and 55 women.
Keywords: TNF; MARKER; Relative Red Cancer